PENGARUH KELUARGA DAN SEKOLAH TERHADAP HASIL BELAJAR MATEMATIKA SISWA DI KELAS VIII MTS NU BATAHAN KABUPATEN MANDAILING NATAL TAHUN AJARAN 2022/2023 - Refdi Refdi; Aniswita Aniswita; Haida Fitri; Tasnim Rahmat (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research was motivated by the low mathematics learning outcomes of class VIII MTs NU Batahan students, namely around 74-94% of the number of students who were still below the KKM. This is thought to be influenced by several factors, including family factors and school factors. Based on these conditions, researchers are interested in conducting research on the influence of family and school on students mathematics learning outcomes in class VIII MTs NU Batahan, Mandailing Natal Regency, Academic Year 2022/2023. This type of research is correlational using the ex post facto method. The results of the research show (1) there is a significant influence of the family on the mathematics learning outcomes of students in class VIII MTs NU Batahan Mandailing Natal Regency for the 2022/2023 Academic Year with a value of tcount > ttable, namely 3.793 > 1.711. (2) there is a significant influence of school on the mathematics learning outcomes of students in class VIII MTs NU Batahan Mandailing Natal Regency for the 2022/2023 Academic Year with a value of tcount > ttable, namely 3.249 > 1.711. (3) there is a significant influence of family and school on the mathematics learning outcomes of students in class VIII MTs NU Batahan Mandailing Natal Regency for the 2022/2023 Academic Year with a value of Fcount > Ftable namely 7.93 > 2.42.